Legal Protection for Buyers Against Developers' Default in Land Purchase Agreements (study of decision number 15/Pdt.G/2025/PN Samarinda): Perlindungan Hukum Pembeli Atas Wanprestasi Developer Tidak Beritikad Baik Dalam Perjanjian Jual Beli Tanah Perumahan (studi putusan nomor 15/Pdt.G/2025/PN Samarinda) - Sasikirana Anastasia; Asnawi Mubarok; Rahmatullah Ayu Hasmiati (Journal of Creative Power and Ambition (JCPA), 2026)
This study analyzes the form of default by a bad-faith developer in housing land sale and purchase agreements based on Decision Number 15/Pdt.G/2025/PN Smr dated 24 July 2025, using normative legal research methods with statute, case, and conceptual approaches. The results show: first, the developer committed default in the form of niet nakomen a total failure to split HGB Certificate Number 19 (now 435) under PT. Mega Sejahtera Utama into individual plot certificates for more than 21 years constructed through mora ex re under Article 1238 KUHPerdata because the certificate-splitting process technically requires only months to complete; Defendant I was declared in contractual default while Defendant II violated administrative-land law obligations as the holder of the master HGB certificate; and the developer's good-faith obligation was violated across all three contractual phases; second, the buyer is protected through three cumulative layers of repressive instruments, namely a granted nakoming claim under Article 1267 KUHPerdata, a court order directing ATR/BPN as a legal substitute for the master HGB holder who cannot be found thereby filling the normative gap in Government Regulation Number 24 of 1997, and satisfaction of all three good-faith buyer criteria under SEMA Number 4 of 2016; however, the buyer is not fully protected because the uitvoerbaar bij voorraad petition was denied under Article 180 HIR and court costs were imposed on the buyer, confirming the existing protection system remains entirely reactive. This research identifies two normative gaps requiring urgent action: the absence of a statutory deadline for developer HGB certificate-splitting obligations and the absence of regulations on land administration continuity when the notary or PPAT dies before completion.